History of cardiac and thoracic surgery The beginnings of thoracic surgery in Poland – a resection of an enormous tumor of the clavicle in Gdañsk in 1730 - Zielinski, Jacek; Jaworski, Radoslaw; Irga-Jaworska, Ninela; Haponiuk, Ireneusz; Jaskiewicz, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
We present the case of a 27-year-old patient with an enormous tumor of the clavicle, who, in 1730, was referred to Ludolf Remmers, a famous Gdańsk surgeon. After clinical evaluation and further consultation with fellow surgeons, Remmers decided to remove the lesion surgically. A detailed description of the procedure and its post-operative period survived to this day, owing to the personal account of Paul Heinrich Moehring, who was present at the surgery. Moehring, a young German physician, botanist, and ornithologist, commenced his medical and anatomical studies in 1729 at the Academic Gymnasium in Gdańsk, Poland. The surgery was the subject of his publicly defended dissertation as part of the final examination, concluding his medical education in Gdańsk.